Identifikasi Perilaku Kenakalan Siswa di SMA Ferdy Ferry Putra Kota Jambi - Trie Utami Lestari; Rasimin Rasimin; Siti Amanah (Departement of Mathematics Education, 2023)
This research is motivated by the phenomenon of student delinquency which is increasingly prevalent in schools, various forms of student delinquency ranging from mild delinquency such as truancy to delinquency that causes victims from other parties such as fighting, brawls, and extortion. This is the basis for the purpose of this study, namely to find out (1). How big is the level of delinquency that causes physical victims at Ferdy Ferry Putra High School, Jambi City?, (2). How big is the level of delinquency that causes material victims for other people at Ferdy Ferry Putra High School, Jambi City?, (3). How big is the level of social delinquency that does not cause victims from other parties at Ferdy Ferry Putra High School, Jambi City?, (4). How big is the level of delinquency against one's own status at Ferdy Ferry Putra High School, Jambi City? The type of research used is quantitative with a descriptive approach. The population and sample in this study were students in class X and XI at SMA Ferdy Ferry Putra, Jambi City, with a total of 82 students. using total sampling technique. To find out the accuracy and validity of this instrument, a percentage test was carried out and with the help of the SPSS 24.00 program. The results showed that the delinquent behavior of students at SMA Ferdy Ferry Putra, Jambi City, was 82.37% at a high level, if you look at the data description indicators as follows (1). Delinquent behavior that causes physical casualties with a total percentage calculation of 80.69% at a high level, (2). Delinquent behavior that causes material victims to other people with a total calculation of 84.14% at a high level, (3). social delinquency that does not cause victims from other parties with a total calculation of 81.89% at a high level. (4). Student delinquency behavior on indicators of delinquency against one's own status with a total calculation of 83.78% at a high level.